Fiscal Policy with Limited-Time Commitment - Alex Clymo; Andrea Lanteri (Tinbergen Institute, 2016)
We consider models where the Ramsey-optimal fiscal policy under Full Commitment (FC) is time-inconsistent and define a new notion of optimal policy, Limited-Time Commitment (LTC). Successive one-period lived governments can commit to future plans over a finite horizon. We provide a sufficient condition on the mapping from finite policy sequences to allocations, such that LTC and FC lead to the same outcomes. We then show that this condition is verified in several existing models, allowing FC Ramsey plans to be supported with a finite commitment horizon (often a single period). We relate the required degree of commitment to the economic environment: in economies without capital, the minimum degree of commitment required is given by the government debt maturity; in economies with capital and government balanced-budget constraints, the required commitment is given by the horizon over which the budget has to be balanced. Finally, we solve numerically for the LTC equilibrium of an economy where the equivalence result fails and show that a single year of commitment to capital taxes provides substantial welfare gains relative to the No-Commitment time-consistent policy.
Keywords: E61; E62; H21; H63; 330; Optimal fiscal policy; time-inconsistency; limited commitment